PERILAKU BULLYING SISWA DITINJAU DARI PERSEPSI POLA ASUH OTORITER DAN KEMAMPUAN BEREMPATI - Sri Suparwi (INFERENSI: Jurnal Penelitian Sosial Keagamaan, 2014)
The purpose of this research is finding the correlation between authoritative teaching and empathy toward bullying in the students of SMP Muhammadiyah in Salatiga. The subjects of this research are among 115 students of the third grade. The finding shows that there is a positive correlation among authoritative teaching and empathy toward bullying.